The Influence of Drill Method on Underhand Serve in Sepak Takraw - Siti Muanisah; Agus Raharjo (Universitas Negeri Semarang, 2026)
This research is motivated by the low accuracy of underhand serves among students in the sepak takraw extracurricular. The purpose of the research is to determine the effect of the drill method on the improvement of underhand serve skills. This research is a quasi-experimental study with a one group pretest-posttest design. The research subjects are the extracurricular students of Citra Kartika Club at SDN 2 Jungsemi. The research instrument uses a sepak takraw service test. The data analysis technique used is the t-test (paired sample t-test). Based on the research data obtained on the underhand serve skill in the game of sepaktakraw among extracurricular students of the Citra Kartika Club at SDN 2 Jungsemi, the pre-test variable with a sample size of 10 students had an average score of 18.70, with a minimum score of 16 and a maximum score of 22. The post-test variable with a sample size of 10 students had an average score of 28.10, with a minimum score of 25 and a maximum score of 30. The t-test results show that drill training has an effect on the Underhand Serve Skill. This can be proven by the significance value of the t-test 0.00 < 0.05. The results of this study are expected to serve as a reference for coaches in improving the quality of basic technical training.